Effect of storage time and temperature on the results of analysis of synovial and mesothelial fluids. (9th June 2016) - Hughes, K. J.; Rendle, D. I.; Higgins, S.; Barron, R.; Cowling, A.; Love, S.; Durham, A. E.
Summary: Reasons for performing study: Delays between collection and laboratory analysis of equine body fluid samples are common in practice; however, the effects of delays on the accuracy of results and diagnostic interpretation are unknown. Objectives: To assess the effects of storage time and temperature combination on protein and cell parameters of equine synovial and mesothelial cavity fluids and determine whether any changes affect clinicopathological interpretation. Study design: In vitro experiment. Methods: Body fluid samples obtained from horses during diagnostic investigation were divided into 7 aliquots and total protein concentration (TP), total nucleated cell count (TNCC) and neutrophil morphology were analysed immediately (T0 ) and at 24 (T24 ), 48 (T48 ) and 72 h (T72 ) after storage at 4 or 22°C. Linear mixed models were used to analyse effects of fluid type and storage conditions on TP, TNCC and neutrophil morphology grade. Changes in interpretation of samples over time and diagnostic performance at each analysis point were recorded. Results: A total of 32 samples were collected from 23 horses. Storage had no effect on TP. Cell count was influenced by fluid type and was significantly reduced at T72 for storage at 4°C and T24, T48 and T72 for 22°C (P<0.001). Neutrophil morphology grade was significantly greater at T24, T48 and T72 than at T0 for both 4 and 22°C (P<0.001). For 9 samples, the diagnostic interpretation changed over time. Specificity and positive predictive value at each analysis point was 100%; however, sensitivity and negative predictive value decreased with greater storage duration and temperature. Conclusions: Alterations in the TNCC and neutrophil morphology of body fluid samples occur when analysis is delayed, especially with higher storage temperatures, and may influence interpretation and clinical decision‐making. Body fluid samples should be analysed as soon as possible after collection to minimise preanalytical errors due to storage.